Effect of vermicompost and chemical fertilizers on growth, yield and quality of coriander (Coriandrum sativum L.) in a semi-arid tropical climate - Singh, Munnu (Journal of Spices and Aromatic Crops, 2011)
Field experiments were conducted at Bangalore (semi-arid tropical climate) to study the influence of vermicompost and chemical fertilizers (NPK and sulphur) on growth, seed and oil yield and oil quality of coriander (Coriandrum sativum). The results of the study showed that application of vermicompost (7.5 t ha-1) + 25% recommended NPK (25 : 12.5 : 12.5 kg ha-1) produced maximum biomass (28.2 q ha-1), seed (10.82 q ha-1) and oil yield (6.53 kg ha-1) of coriander which was at par with other treatments except full organic manure and control which indicated that 75% NPK requirement can be supplemented through vermicompost without loss of yield. The oil content and quality were not influenced by the treatments tested.